2009
DOI: 10.1152/ajpgi.00446.2007
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal ontogeny of intestinal GCPII and the RFC in pig

Abstract: In humans and pigs, hydrolysis of dietary polyglutamyl folates is carried out by intestinal brush border folate hydrolase [glutamate carboxypeptidase II (GCPII)], whereas the transport of the monoglutamyl folate derivatives occurs via the intestinal brush border reduced folate carrier (RFC). The study objective was to measure the expression of intestinal GCPII and RFC during postnatal development of pigs and their effects on plasma and liver folate concentrations. Duodenum, jejunum, ileum, liver, and plasma sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In addition, liver mRNA abundance of FADS2, ELOVL5, and FADS1 precipitously dropped from d 0 to 4 and did not recover to the initial d 0 values throughout the first 16 d of life. These results are congruent with literature reports showing, first, that FADS2 and FADS1 increase in liver throughout gestation (27) and second, that many genes with metabolic involvement in pigs show a similar pattern of rapid decline following birth and rebound several weeks later (28,29). In fact, Clandinin et al (30) demonstrated developmental increases in the ability of pig fetuses to synthesize trienes, tetraenes, and penteanes from preterm (60 d gestation) to full-term.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, liver mRNA abundance of FADS2, ELOVL5, and FADS1 precipitously dropped from d 0 to 4 and did not recover to the initial d 0 values throughout the first 16 d of life. These results are congruent with literature reports showing, first, that FADS2 and FADS1 increase in liver throughout gestation (27) and second, that many genes with metabolic involvement in pigs show a similar pattern of rapid decline following birth and rebound several weeks later (28,29). In fact, Clandinin et al (30) demonstrated developmental increases in the ability of pig fetuses to synthesize trienes, tetraenes, and penteanes from preterm (60 d gestation) to full-term.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the fact that piglets were fed the NRC-recommended amount of folate, they had very low RBC folate concentrations and high homocysteine concentrations, characteristic of suboptimal folate status in humans. These concentrations, however, were similar to those reported in the literature for piglets (23,(60)(61)(62). A high plasma homocysteine concentration in piglets is thought to be due to their very rapid rate of growth, which creates a high demand for S-adenosylmethionine (product of a reaction between methionine and the enzyme methionine adenosyltransferase), which serves as a universal carbon donor in the body and specifically for creatine synthesis (63).…”
Section: Discussionsupporting
confidence: 83%
“…Hydrolysis of the polyglutamyl form of folate (mainly from diet) occurs primarily in the brush border of the proximal small intestine in humans and pigs by glutamate carboxypeptidase II (GCPII) (23,54). Very little is known about the regulation of GCPII in the distal bowel (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher expression of Slc19a1 transcripts was detected in suckling rats compared with weanling or adult animals (Balamurugan and Said, 2003). Shafizadeh and Halsted (2009) recently showed that Slc19a1 mRNA transcripts were present in the small intestine at birth and declined significantly throughout development to 6 months in pig. Balamurugan et al (2007) also found that there was a gradual decrease with development in the abundance of mRNA and protein of a specific folate transporter (encoded by folt-1 gene) in the intestine of nematodes.…”
Section: Discussionmentioning
confidence: 98%